Organizational reputation risk management as a component of the dynamic capabilities management process = Zarządzanie ryzykiem reputacji organizacyjnej jako składowa procesu zarządzania dynamicznymi zdolnościami - Krzakiewicz, Kazimierz; Cyfert, Szymon (Zielona Góra: Faculty of Economics and Management Press)
Intangible assets, such as reputation, brand value, strategic position, alliances, knowledge, human capital, play an increasingly important role in shaping the market value of an organization. At the same time, in the literature it is emphasized that the attribute of intangibility translates into an increased risk of destruction or impairment of assets.
Keywords: zgodności dynamiczne; ryzyko reputacyjne; ryzyko reputacji organizacyjnej; zarządzanie ryzykiem; dynamic capabilities; reputational risk; organizational reputation risk